Open government studies: A Bibliometric analysis - Afandi, Syed Agung; Erdayani, Rizki; Afandi, Muslim; Lestari, Reski (Journal of Law, Administration, and Social Science, 2024)
The aim of this research is to analyze open government research bibliometrics. This research uses a qualitative approach with bibliometric analysis methods. The data used in this research is of secondary type, originating from the Scopus database. Data was collected using the Publish or Perish application using the keyword "open government". The data obtained was then analyzed using the Vosviewer application to obtain a bibliometric map generated from keywords for all papers. Based on the results of this research, there were 160 papers over a period of 37 years. The first open government paper was published in 1986. There were 241,891 citations, 146 h-index, and 150 g-index, which shows that this paper has high impact and productivity. In this paper, there are 137 keywords grouped into 16 clusters. From these keywords, 2056 total link strengths and 567 occurrences were obtained. The keywords that dominate this paper are e-government, collaborative governance, transparency, public participation, and accountability. This shows that global open government research focuses on these concepts.